"In vitro" capacitation and further progesterone‐induced acrosome exocytosis are linked to specific changes in the expression and location of threonine phosphorylation of boar spermatozoa. Issue 8 (25th June 2019) - Ramió‐Lluch, Laura; Prieto, Olga Blanco; Ramírez, Alfredo; Fernández‐Novell, Josep M.; Peña, Alejandro; Rodríguez‐Gil, Joan Enric
Abstract: The aim of this study was to determine if the achievement of the "in vitro" capacitation (IVC) status and subsequent progesterone‐induced "in vitro" acrosome exocytosis (IVAE) was accompanied with overall changes in threonine phosphorylation (pThre) of boar spermatozoa. For this purpose, mono‐ and bi‐dimensional Western blot analyses as well as immunocytochemistry studies against pThre were performed in boar sperm subjected to IVC and subsequent IVAE. Mono‐dimensional Western blot in non‐capacitated samples showed that launching of IVC did induce an overall increase in signal intensity in all observed bands that was followed by a subsequent decrease afterwards. Bi‐dimensional Western blot analysis showed the presence of four main signal protein clusters. The attainment of IVC induced an overall decrease in the number and intensity of spots of Clusters A, B and C and a concomitant increase in the intensity of spots of Cluster D. The IVAE launching caused a rapid increase in the intensity of spots of Clusters B, C and D, which was followed by a subsequent decrease of the intensity together with a concomitant pI displacement of Cluster C. Finally, immunocytochemistry showed that the pThre signal of non‐capacitated cells was located at the whole sperm. The IVC did not induce prominent changes in this location. In contrast, the induction of IVAE caused the appearance of an additional an intense acrosome and tail pThre signal that subsequently decreased. In conclusion, our results indicate that IVC and further IVAE induced specific changes in the intensity and appearance of pThre protein phosphorylation which were linked to changes of specific protein characteristics as pI. These results support, thus, the existence of a specific role of pThre in IVC/IVAE of boar sperm.